Factors that contribute to the cyberbully activities among students using social media: case study in Universiti Teknologi MARA (UiTM) Seremban 3, Negeri Sembilan / Nurul Aimi Athirah Amriyanto and Siti Marliza Aman - Amriyanto, Nurul Aimi Athirah; Aman, Siti Marliza (2022)
Cyberbullying, as a serious form of repetitive, purposive, and harmful aggressive behaviour, must be addressed. Cases of cyberbullying are becoming more common in Malaysia. It frequently occurs between students. Cyberbullying is an act in which the abuser proposes information and actions with the intent of psychologically harming an individual or group. This research focused on university students in Universiti Teknologi Mara (UiTM) in Seremban 3. A survey was conducted with 366 students. The objective of this research is to determine the factors that contribute to the cyberbullying activities among students using social media by looking at peer influence, attitude and family background. Regarding the various technologies and platform social media users experienced significantly more to the cyberbullying. The survey also indicated that students spent more time on social media. The researcher used a descriptive style by using a questionnaire to scrutinize the factor that contributes to the cyberbully activities. Based on the result, it shows that family background is most significant towards the cyberbully activities among students. Family is the one of the most constant and influential aspects in the child environment. Parental participation is linked to the behaviour of the children.